L’icnoassociazione a tetrapodi del Bletterbach (Trentino Alto-Adige) e le sue relazioni con gli ecosistemi terrestri di fine Permiano - Bernardi, Massimo (2017)
In this paper we provide an updated review of the tetrapod footprint association discovered in the Bletterbach Gorge (Southern Alps, NE Italy) from the ‘70s. We provide global-scale analysis integrating paleontological and climatic data highlight the importance of the Bletterbach ichnoassociation as key reference for low-latitude terrestrial ecosystems during the Lopingian (Late Permian). Our results provide evidence for a tight correlation between the distribution of the main herbivorous tetrapod clades (dicynodonts, pareiasaurs, captorhinids) and the latitudinal climatic zonation.